The acute adverse health effects of kratom: an evaluation of case reports - Smallets, Sarah; Litvin, Sydney; Abele, Grayson; Kirsh, Sarah; Paustenbach, Dennis (Frontiers in Pharmacology, 2025)
Mitragyna speciosa, commonly known as kratom, has gained popularity in the United States due to its stimulant and analgesic effects. Allegations of kratom-associated adverse health effects, primarily based on case reports/series, have obtained media attention. Thus, a systematic literature search using PubMed was conducted to identify patterns among cases involving kratom use and acute adverse health effects in humans. 95 patients were identified for review. Mitragynine presence was toxicologically confirmed in 55 cases; 35 were deceased (mitragynine blood levels ranged from 3.5 to 7,500 ng/mL), and 20 were living (range of 5 to 340 ng/mL). Reported adverse effects included pulmonary, cardiovascular, brain, liver, kidney, and gastrointestinal effects, as well as seizures, loss of consciousness, lethargy, fatigue, and altered mental state. Toxicology panels revealed confounding substances that could have caused or contributed to the acute adverse effects in 32 deceased and seven surviving cases (p = 0.0002), despite attribution of many adverse effects solely to kratom. Upon analysis of the identified case reports, a pattern of weak or inadequate toxicology testing and medical history was observed. Currently, the literature provides insufficient evidence to support the claim that kratom consumption alone increases the risk of severe acute adverse health effects. More research is necessary to isolate the effects of kratom from those of polypharmacy.